2021
DOI: 10.3390/geriatrics6040096
|View full text |Cite
|
Sign up to set email alerts
|

Pet-Assisted Therapy for Delirium and Agitation in Hospitalized Patients with Neurocognitive Impairment: A Review of Literature

Abstract: Delirium leading to agitation is a common issue in elderly people and patients with underlying neurocognitive impairment. Despite use of medications to treat agitation, polypharmacy is a major concern and might lead to multiple side effects in this patient population. Therefore, it is imperative to investigate non-pharmacological methods that can provide solutions to the problem. The objective of this review was to evaluate the impact of pet-assisted therapy on elderly patients, with a major focus on agitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In fact, the group of treated subjects had a slowdown in cognitive decline, an increase in functional daily life skills (compared to controls that showed a deterioration) and a reduction in behavioral and stress disorders. In the following years, other studies conducted on small groups of patients confirmed these findings, including, among other things, a reduction in pathological behaviors (particularly in daytime hours), reduced agitation and an increase in some socializing behaviors (smiles, interactions and verbalization) [ 25 , 26 ]. However, the sporadicity of studies in this field and the presence of various methodological problems have, as a consequence, caused there to still be no certainty regarding the specific effects of AAT.…”
Section: Introductionmentioning
confidence: 74%
“…In fact, the group of treated subjects had a slowdown in cognitive decline, an increase in functional daily life skills (compared to controls that showed a deterioration) and a reduction in behavioral and stress disorders. In the following years, other studies conducted on small groups of patients confirmed these findings, including, among other things, a reduction in pathological behaviors (particularly in daytime hours), reduced agitation and an increase in some socializing behaviors (smiles, interactions and verbalization) [ 25 , 26 ]. However, the sporadicity of studies in this field and the presence of various methodological problems have, as a consequence, caused there to still be no certainty regarding the specific effects of AAT.…”
Section: Introductionmentioning
confidence: 74%
“…Recent advances in objective assessment tools for POD include glucose metabolism evaluation via positron emission tomography (PET) [ 7 ], neuroimaging techniques [ 8 ], and electroencephalography (EEG) [ 9 ]. Despite their potential, the implementation of such tools, especially EEG, in clinical settings remains inconsistent, reflecting the need for more reliable indicators tailored for pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Pets, as a type of companion animal in intimate contact with humans, have a positive effect on human mental health, such as relieving neurological disorders, anxiety, depression, and also reducing loneliness in the elderly [ 1 , 2 ]. However, pets, on the other hand, are vectors of some pathogenic microorganisms, and antibiotic resistance caused and spread by pets creates a serious public safety risk [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%